PELAKSANAAN PERJANJIAN KREDIT MODAL USAHA ANTARA USAHA EKONOMI DESA/KELURAHAN DENGAN MASYARAKAT KOTA PEKANBARU - Ridho Alamsyah; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The economic development of a region's community is seen from how many people live below the poverty line, the cause of poverty is the absence of income from each of these communities. For people who want to apply for a loan to get a business capital loan from the Savings and Loans Village Economy Business (UEK-SP) is by entering into an agreement between the community (Debtor) and Savings and Loans Village Economy Business (UEK-SP) in this case as a creditor.This type of research can be classified in the type of sociological (empirical) legal research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted in the Savings and Loans Village Economic Business (UEK-SP) Pekanbaru City, because every kelurahan in Pekanbaru had Savings and Loans Village Economic Enterprises while the population and sample were the Chairman of the Savings and Loans Village Economy Business in Pekanbaru City, Head of Community Empowerment Section Mayor Office Pekanbaru and Chair of the Pekanbaru City Urban Empowerment Program. Data sources used are primary data and secondary data. Data collection techniques in this study were interviews, and literature reviewThe conclusions that can be obtained from the results of the study are First, the Economic Status of Savings and Loans Village Businesses (UEK-SP) has been regulated in the Governor Regulation and Permendagri Number 06 Year 1998 Concerning Economic Savings in Village Savings and Loans (UED-SP). Only the status as a legal entity or not is still not clearly and firmly regulated. Second, the Savings and Loans Village Economy Business (UEK / D-SP) can carry out savings and loan activities.and Third, the inhibiting factors for the implementation of savings and loan agreements for the economy of urban village savings and loans (UEK-SP) consist of Status (UEK / D-SP), savings and loan agreements (UEK / D-SP) require a long time, customer loan installment payments do not everything is smooth, Guidance and Supervision of the Credit Capital Business Customers are less than optimal, and Financial ResourcesKeywords: Implementation, Credit Agreement, Business Capital, Village Economy Business, Savings and Loans, Community, Pekanbaru.